Criminal justice: a New Zealand introduction - Gilbert, Jarrod; Newbold, Greg (Auckland University Press, 2017)
An introduction to New Zealand's criminal justice system - from crime and policing to the courts - aimed at students and general readers. In this major new textbook, leading scholars from criminology, history, journalism, law, psychology, sociology and other fields take us inside New Zealand's criminal justice system. The authors begin with an introduction to the history and current state of crime, policing and prisons in New Zealand; they then explain the workings of criminal procedure, from evidence to sentencing; and finally they address key current issues such as Maori and the justice system, youth and gangs, psychology and the media. This book tackles the big questions: How can crime be explained? Is crime rising or falling and if so, why? How do the police operate? How do the courts work? What is the meaning of a `life' sentence? What is the link between crime and mental instability? Why are Maori over-represented in the criminal justice system? How do we deal with youthful offenders? How do judicial miscarriages arise? Do the stories we read about crime in the media reflect reality? And how does justice operate in the criminal underworld? This book is an important new introduction to New Zealand's criminal justice system